An analysis of restrictive mechanisms on director behavior regarding corporate philanthropy in China. Issue 3 (9th May 2016) - Feng, Li; Zhang, Rong; McCornac, Dennis
Abstract : Purpose: Currently, in China, the governance structure of modern companies gives directors great powers to pursue profits. However, little attention is paid to the undertaking of corporate philanthropic activities. Therefore, rules on directors' behavior in terms of corporate philanthropy are urgently needed to resolve the conflict between philanthropy and profits. This paper aims to discuss the main purpose of corporate philanthropy behavior in China, namely, the promotion of the company, and to analyze the theoretical mechanism for placing restrictions on directors' behavior. The concepts and details of directors' duty of loyalty and duty of diligence are also discussed. Design/methodology/approach: The paper addresses the theoretical framework for the restriction of director behavior in corporate philanthropy in China, explains the legal dilemma for the current situation and analyzes the problems associated with the determination of board directors' behavior. Findings: It is concluded that board members should give priority to their duty of loyalty and comply with their faithful obligations in corporate philanthropy. They should also fulfill their diligence obligations and not cause inconvenience and trouble for the company. Research limitations/implications: Corporate philanthropy is well known as a beneficial activity to both the company and society. It not only helps to establish a good image of the company, which is in line with the interests of the shareholders and creditors, but also contributes to the development of social welfare. It is a topic worthy of deep discussion. Practical implications: It is still very difficult to establish non-profit organizations because of stringent conditions on registration, organization and funding in China. Therefore, there are a limited number of independent non-governmental charitable organizations in China. Most charitable organizations have charitable expertise and government ties. Corporate philanthropy is a problem closely related to governmental administration and legal system renovation. Social implications: Recently, a young girl related to the Red Cross Society of China was found guilty and arrested. This scandal has made people lose their confidence in philanthropy and has caused another round of intense discussion online. Corporate philanthropy is the focus of criticism because individuals with power gain benefits by taking advantage of their position. It is a very challenging issue for the Chinese society as to how to restore the reputation of philanthropy. Originality/value: This paper points out the weakness in the current legal system as a restrictive mechanism to supervise the board directors' behaviors in China. It analyzes the corporate philanthropy issue from the national level and highlights the significance of supervising governmental administration and corporate management through the improvement of the legal system.